Ways to Improve Fire Safety Measures in Cotton Ginning Factories - Habibullaevna, Kochkarova Cholpanoy; Oghly, Omonboev Dyorbek Oybek (International Journal on Human-Computing Studies, 2023)
Wide-scale reforms are being implemented to ensure the safety, life and health of a person, as well as the ability to work, during the work process. In particular, the implementation of the four main powers in the field of labor protection, the transfer of labor protection services to professional participants of the market, and the strengthening of state and public control over labor protection are primarily aimed at improving working conditions in enterprises and organizations, at workplaces. aimed at preventing injury during discharge.